Determinants of Non-Organic Employee Performance: A Study at the Bank Indonesia Representative Office in South Sumatra - Nurkolis, Nurkolis; Asiati, Diah Isnaini; Choiriyah, Choiriyah; Sule, Sani Abdullahi (Universitas Muhammadiyah Palembang, 2025)
Non-organic employees have an important role in supporting the operations of the Bank Indonesia Representative Office. However, challenges such as low motivation, less supportive work environment, and limited competence have the potential to reduce performance. This study aims to analyze the effect of motivation, work environment, and competence on the performance of non-organic employees at the Bank Indonesia Representative Office in South Sumatra Province. This study uses a quantitative approach with a population of 133 using the Slovin formula to obtain a sample of 100. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS. The results of the study indicate that partially and simultaneously, motivation, work environment, and competence have a positive and significant effect on employee performance. These findings provide important implications for management to develop strategies to increase motivation, improve the work environment, and strengthen the competence of non-organic employees.